The use of email to communicate with patients in the Porta do Sol Family Health Unit (Portuguese Journal of Family Medicine and General Practice, 2011)
Aim: To characterize the e-mail messages sent between patients and physicians and between patients and medical secretaries in a family health unit (FHU.) Type of study: Cross sectional study. Setting: USF Porta do Sol, Matosinhos, Portugal Population: Electronic mail messages exchanged between the eight doctors and their patients and between the six clinical secretaries and the patients of the family health unit. Method: An analysis of electronic mail sent between September 2009 and February 2010. The variables studied were the sender of the message, the subject matter of the message, the time between the message and the response and time of sending the message. Results:We received 549 medical electronic messages (an average of 74.2 per physician) in the study period. The issues most frequently discussed were medical issues, administrative issues and diagnostic tests. Most messages addressed only one subject (84.9%). Most responses (50.1%) were sent between 0 to 12 hours after receipt of the message. 85.9% of the messages were sent during operating hours of the USF. The secretaries received 49 messages. The issues most frequently discussed were administrative issues such as appointments (58.3%). The most frequent time interval between receipt of the message and the response was between 0-12h (57.1%). All messages and responses were sent during the operating hours of the USF. Conclusion: For e-mail messages sent to physicians, the number and type of issues discussed are similar to those found in previously published studies. This study presents new data with respect to messages sent to and from medical secretaries. It helps to understand the importance of email as a communication tool in health services.
Keywords: Electronic Mail; Communication; Primary Health Care